Chlamydia pneumoniae in atherosclerotic lesions associated with acute myocardial infarction - Woolcott, Orison (2001)
OBJECTIVES: To determine the association between Chlamydia pneumoniae and atherosclerosis in arteries involved in acute myocardial infarction. MATERIAL AND METHODS: Subjects 70 years old or younger whose cause of death was acute myocardial infarction and subjects whose cause of death was not acute myocardial infarction were studied, all of them necropsied 12 to 48 hours after death. Detection of C. pneumoniae in atherosclerotic lesions was done by immunohistochemistry. RESULTS: Thirty-five subjects were included, thirty of them males. There were 13 cases of myocardial infarction, and 22 controls. The proportion of positive specimens was higher in cases, 69,2%, than in controls, 22,7% (OR 4,8; 95% confidence interval [CI] 0,9-24,6, p =0,061). Chlamydia pneumoniae was found in 21% of mild atherosclerosis lesions and in 62,5% in moderate and severe lesions (OR 3,8; CI 0,7-21,8, p =0,129). CONCLUSIONS: We found a positive association between C. pneumoniae and acute myocardial infarction. These findings suggest that C. pneumoniae is implicated in instability of the atherosclerotic plaque.